Aqueous Ferriferous Scavenging with Waste Plastic-Cellulose Composite for Remediation (International Journal of Latest Technology in Engineering Management & Applied Science, 2024)
Abstract: This work was conducted to investigate the adsorptive removal of iron (III) ions from simulated and ferriferous water using unmodified and modified waste PET-bottle/coconut husk composites. The waste PET-bottle/coconut husk composites were prepared by melt mixing and modified using ferric and ferrous chloride. The composites were characterized using the Fourier Transform Infrared (FTIR) spectroscopy. The adsorption process was carried out using batch method while residual adsorbate concentration in solution was determined using Atomic Absorption Spectroscopy (AAS) analysis. The residual equilibrium concentrations results were applied to the kinetics, equilibrium and intraparticle diffusion analyses. The kinetics results of the adsorption showed that the most fit model based on the R2 values for the unmodified is the second order with a value of 0.79, while that of the modified composite correlated with the pseudo first order with an R2 value of 0.95. The highest rate constant was 2.29 g/mg min for PFO for the unmodified implying the shortest exposure and contact time per unit mass of adsorbent. The Freundlich and Sips isotherm models both correlated at 97% with the unmodified composite, while the Freundlich model was the most fit model for the modified composite with an R2 value of 0.87. Qmax calculated from Langmuir isotherm was 6657.91 and 7939.32 mg/g for unmodified and modified composites respectively, indicating a higher sorption potential for the modified composite. The modified composite gave a far higher and near unity R2 value of 0.96 for intraparticle diffusion than the unmodified composite with 0.46.